Dysregulated Bone Metabolism Is Related to High Expression of miR-151a-3p in Severe Adolescent Idiopathic Scoliosis. (27th September 2020) - Wang, Yunjia; Zhang, Hongqi; Yang, Guanteng; Xiao, Lige; Li, Jiong; Guo, Chaofeng
Abstract : Adolescent idiopathic scoliosis (AIS) is a common complex disease, and bone homeostasis plays an important role in its pathogenesis. Recent advances in epigenetic research show that dysregulated miRNAs may participate in the development of orthopedic diseases and AIS. The aim of this study was to detect differentially expressed miRNAs in severe AIS and elucidate the mechanism of miRNA deregulation in the pathogenesis of AIS. In the present study, miRNA expression profiles were detected in severe and mild AIS patients as well as healthy controls by miRNA sequencing. Candidate miRNAs were validated in a larger cohort. Primary osteoblasts from severe AIS patients were extracted and isolated to determine the effect of the candidate miRNAs on bone metabolism. Finally, we determined the methylation level in primary osteoblasts from severe AIS patients. The result showed that miR-151a-3p was overexpressed in severe AIS patients. Reduced GREM1 expression was observed in primary osteoblasts from severe AIS patients. miR-151a-3p directly inhibited GREM1 in primary osteoblasts. Relatively lower methylation levels were detected in primary osteoblasts from severe AIS patients. In conclusion, our study revealed that plasma miR-151a-3p levels may serve as a biomarker for severe AIS. Overexpression of miR-151a-3p may interrupt bone homeostasis via inhibiting GREM1 expression. Our result may provide a new biomarker for the early detection of AIS and increase our understanding of the pathogenesis of AIS.